The importance of vocabulary in language learning and the vocabulary teaching techniques used by Teachers of the Teens English Program at CENIUES, Academic Year 2018 - Guardado Guardado, Yesica Michel; Romero Fuentes, Ana Coralia; León Alvarado, Henrry Bladimir (2024)
This research aimed to highlight the importance of vocabulary and the different vocabulary teaching techniques used to teach English vocabulary to teenage students. Although the importance of vocabulary had been neglected for many decades, during the 80s it became a captivated topic for researchers. So, this study would provide a list of techniques that could be implemented when teaching English vocabulary. The vocabulary teaching techniques are tools that English teachers must use to help students develop their vocabulary. In this study, the teacher´s role was very important because students’ learning depends not only on what they are taught but also on how they are taught. Therefore, this research was related to education, and it was carried out through a descriptive method and a qualitative study which would provide the necessary information for its development. This work presents some theories that back up the idea that lexical knowledge is central to English communicative competence. It has been observed that many English learners who have not developed their vocabulary struggle a lot when stablishing a conversation. That is why, teachers and students played a vital role in this research work. Teachers need to be aware that students learn in different ways and that using effective vocabulary teaching techniques will have a big impact in their progress. On the other hand, students have to identify which techniques really help them retain new words, and they need to develop their own learning strategies, this will allow them to learn in a more effective way. In this piece of work, researchers seeked to identify the vocabulary teaching techniques used by teachers of the English program named Centro de Enseñanza de Idiomas Extranjeros de la Universidad de El Salvador (CENIUES), specifically teachers of the teens English program. In such language program, they not only teach English but also other languages such as French, Japanese and Italian. CENIUES offers classes to children, teens and adults. To collect the data for this research, the research techniques that were used are: observations and surveys; furthermore, the instruments that helped this research are: a check-list and two questionnaires. At the end, the information collected was tabulated and interpreted by the researchers. Thus, the people who participated in the research process were teachers, teenage students of CENIUES and the researchers. To get the necessary information, the researchers formulated some research questions which were the main focus of the study, such questions were oriented on knowing the role of the teacher when instructing vocabulary, knowing the vocabulary teaching techniques that help students learn a word faster, identifying the vocabulary teaching techniques that are more effective when working with teenagers, and others. Accordingly, it is recommended for teachers to spend more time helping learners develop their stock of vocabulary such as phrases, and less time on grammatical structures; to make use of different techniques to introduce vocabulary, to provide students with enough opportunities to encounter words in different contexts, and to adjust their vocabulary teaching methods and techniques according to the level of the students. Effective teachers do not use the same set of vocabulary teaching techniques for every lesson, instead what effective teachers do is constantly reflect about their work, observe whether students are learning or not, and then adjust the vocabulary teaching techniques accordingly. To sum up, when learning English there are many language skills and sub skills that need to be mastered, and vocabulary is one of those sub skills; therefore, the elaboration of this research work would allow the researchers to come up with some final conclusions and recommendations about the vocabulary teaching techniques use in English classrooms when working with teenage students.